1995
DOI: 10.1093/jnci/87.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Angiogenesis and Murine Hemangioma Growth by Batimastat, a Synthetic Inhibitor of Matrix Metalloproteinases

Abstract: These results confirm the importance of matrix metalloproteinase in endothelial cell recruitment that occurs in angiogenesis and in the formation of vascular tumors and suggest a therapeutic potential for synthetic matrix metalloproteinase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
1
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(99 citation statements)
references
References 0 publications
6
91
1
1
Order By: Relevance
“…1). Similar anti-invasive properties have previously been reported with other hydroxamic acid based MMPIs [35][36][37] and TIMPs [38][39][40], as well as with anti-gelatinases anti-bodies [39,41]. Because a reduced invasiveness could result from a cytotoxic effect of the inhibitor, cellular viability and metabolism were measured by the WST-1 assay after 48 h of treatment.…”
Section: Anti-invasive Activity Of Gi129471 On Ht1080 Cellssupporting
confidence: 64%
“…1). Similar anti-invasive properties have previously been reported with other hydroxamic acid based MMPIs [35][36][37] and TIMPs [38][39][40], as well as with anti-gelatinases anti-bodies [39,41]. Because a reduced invasiveness could result from a cytotoxic effect of the inhibitor, cellular viability and metabolism were measured by the WST-1 assay after 48 h of treatment.…”
Section: Anti-invasive Activity Of Gi129471 On Ht1080 Cellssupporting
confidence: 64%
“…For invasion, filters were coated with a thick layer of the reconstituted basement membrane Matrigel (Beckton Dickinson, Bedford, MA, USA; 0.5 mg ml À1 ) that cells have to degrade in order to reach and migrate through the filter. In this assay, invasion is prevented by inhibitors of matrix-degrading proteases, which do not affect chemotaxis (Taraboletti et al, 1995), therefore proving the true functional distinction between the assays of invasion and chemotaxis. Human umbilical vein endothelial cells were detached and treated with vehicle or aplidine (0.03 -10 nM) for 1 h at 371C in DMEM -0.1% BSA.…”
Section: Endothelial Cell Motility and Invasion Assaysmentioning
confidence: 74%
“…This indicates that batimastat inhibition occurred at > 10 days of tumour growth, possibly during the phase when neovascularisation may have been maximal. In a previous model it has been shown that batimastat has the potential to inhibit angiogenesis (Taraboletti et al, 1995).…”
Section: Methodsmentioning
confidence: 99%